The suitability of animated pedagogical agents (APA) characters in teaching and learning - Suzilawati Ibrahim, 1978-; Dayang Tiawa Awang Hamid, supervisor; Fakulti Pendidikan (2010)
Thesis (Sarjana Pendidikan (Teknologi Pendidikan)) - Universiti Teknologi Malaysia, 2010